The Pandemic H30 Subclone of Escherichia coli Sequence Type 131 Is Associated With Persistent Infections and Adverse Outcomes Independent From Its Multidrug Resistance and Associations With Compromised Hosts - Johnson, James R. (Clin Infect Dis, 2016)
Background. The H30 subclone within Escherichia coli sequence type 131 (ST131-H30) has emerged rapidly to become the leading antibiotic-resistant E. coli strain. Hypervirulence, multidrug resistance, and opportunism have been proposed as explanations for its epidemic success. Methods. We assessed 1133 consecutive unique E. coli clinical isolates from 5 medical centers (2010–2011) for H30 genotype, which we compared with epidemiological and clinical data extracted from medical records by blinded reviewers. Using univariable and multivariable logistic regression analysis, we explored associations of H30 with underlying host characteristics, clinical presentations, management, and outcomes, adjusting for host characteristics. Results. The H30 (n = 107) isolates were associated with hosts who were older, male, locally and systemically compromised, and healthcare and antibiotic exposed. With multivariable adjustment for host factors, H30 lost its numerous significant univariable associations with initial clinical presentation, but remained strongly associated with clinical persistence (odds ratio [OR], 3.47; 95% confidence interval [CI], 1.89–6.37), microbiological persistence (OR, 4.46; 95% CI, 2.38–8.38), subsequent hospital admission (OR, 2.68; 95% CI, 1.35–5.33), and subsequent new infection (OR, 1.73; 95% CI, 1.01–3.00). These host-adjusted associations remained strong even with added adjustment for resistance to the initially prescribed antibiotics, and the adverse outcome associations (subsequent hospital admission, new infection) were independent of clinical and microbiological persistence. Conclusions. In addition to targeting compromised hosts and resisting multiple antibiotics, H30 isolates may have an intrinsic ability to cause highly persistent infections and later adverse outcomes. The basis for these host- and resistance-independent associations is unclear, but they should be considered when managing patients with H30 infections.